EFL learners’ experience of a MALL-based vocabulary learning tool - Alhadiah, Abdullah (Universitas Pendidikan Indonesia, 2020)
Since vocabulary learning plays a crucial role in the journey of language learning, various programs and mobile applications have been developed to assist vocabulary learning. However, the effectiveness of MALL-based (mobile-assisted language learning) tools can be determined by examining the perception of users, who are learners in this case, because, as Beres (2011) emphasized, learners do not always perceive learning tool effectiveness in the same way as educators. Thus, the primary purpose of this study is to investigate the perspectives of learners regarding the use of one of the programs that can be used for vocabulary learning — Quizlet. The perceptions of thirty-eight Saudi EFL (English as a Foreign Language) freshmen college students regarding the use of Quizlet for fourteen weeks were examined using questionnaires and interviews. The main findings of the study show that the students demonstrated positive attitudes towards the use of Quizlet in English vocabulary learning. They perceived it as a useful program that was easy to use, and they reported the intention to use it in the future. The present study highly recommends the use of MALL-based tools for vocabulary learning for their usefulness inside and outside the classroom.